The impact of perioperative oral supplementation with immunomodulating diets on postoperative period in patients with major gastrointestinal surgery - N G Panova (RUDN Journal of Medicine, 2012)
Perioperative administration is an important period for nutritional status management. The aim of the study was to assess the impact of perioperative oral immunomodulating diets supplementation in 41 patients after elective major gastrointestinal surgery. Perioperative oral immunomodulating diets supplementation with glutamine and Ω-3 fatty acids during 5 days before surgery enchanced the immune status of the patients,reduced the duration of ICU and hospital stay, and decreased the incidence of postoperative infectious complications.